The extracellular vesicles secreted by lung cancer cells in radiation therapy promote endothelial cell angiogenesis by transferring miR-23a - Yongfa Zheng; Liang Liu; Cong Chen; Pingpo Ming; Qin Huang; Changhu Li; Dedong Cao; Ximing Xu; Wei Ge (PeerJ, 2017)
Angiogenesis is an important factor contributing to the radioresistance of lung cancer. However, the associated mechanisms underlying radiotherapy-induced pro-angiogenesis are unclear. Here, we demonstrated that Extracellular vesicles (EVs) derived from cultured cells in vitro enhanced HUVEC proliferation and migration, and the enhancement effect became more obvious when HUVECs were treated with EV derived from A549 or H1299, two lung cancer cell lines. Additionally, the pro-angiogenesis effect induced by EV could be strengthened when the lung cancer cells were exposed to X-ray irradiation. Furthermore, we verified that the downregulation of PTEN plays a vital role in this process. By evaluating the changes in the levels of microRNAs(miRNAs) targeting PTEN in EV, we found that miR-23a was significantly upregulated and mediated a decrease in PTEN. A luciferase reporter gene transfer experiment demonstrated that PTEN was the direct target of miR-23a, and the kinetics of PTEN expression were opposite to those of miR-23a. Our results show that the miR-23a/PTEN pathway plays an important role in EV-induced angiogenesis. These findings implicate the miR-23a/PTEN axis as a novel therapeutic target for lung cancer radiotherapy.